Mental health experience in primary health care: a psychosocial vision focused on territory - Jeisa Barbosa Diniz (Revista Enfermagem Digital Cuidado e Promoção da Saúde, 2019)
Objective: This study aims to report the work experience of a primary health nurse from a Psychosocial Care Network (PCN) on a Family Health and Primary Care Extended Center located in Recife-PE (Brazil). Methods: This study reports a work described in a field journal between June and October of 2019. It details activities of four family health units and their medical staff during this period. We commit to respect all ethical aspects according to brazilian Ministry of Health resolution no. 510/2016. Results: We registered various providing cares, groups, meetings, and general day-to-day activities as well as particularities of each FCU. Among the 67 patients on the study, most of them were female and their psychological complaints were related to social concerns. Conclusion: It was observed the importance of a shared work, the need of an extension of the services offered in the Psychosocial Care Network, and the need of more mental health specialisation for basic care workers.